Pengenalan Navigasi Dasar dan User Interface Coretax untuk Dosen dan Tendik Akper HKJ - Sihar Tambun; Riris Rotua Sitorus (Jurnal Pemberdayaan Nusantara, 2026)
Mastering tax regulations and tax reporting through CoreTax is crucial for taxpayers, both individual and corporate taxpayers. Understanding taxes and developing tax reporting skills through CoreTax will encourage and improve taxpayer compliance. The purpose of this CoreTax education activity is to improve the understanding of lecturers and educational staff at the Husada Karya Jaya Nursing Academy. The method used in this CoreTax education is a service learning method, specifically a lecture method followed by direct practice on the CoreTax website. The activity stages start from the preparation stage, the implementation stage of the CoreTax education, and the evaluation stage. This activity successfully increased the participants' understanding of CoreTax and how to report it. However, this CoreTax education must be sustainable by means of participants actively practicing reporting taxes through CoreTax.